Overview of US Tahiti Lime Production and Markets: Trade and Consumption Analysis - Trent Blare; Fredy BALLEN; Jonathan Crane (EDIS)
Key and Tahiti limes have historically been very important to the economy of south Florida. However, there are few commercial orchards left for these lime cultivars in the state. Many orchards were destroyed during Hurricane Andrew, and those that survived were then eliminated by Florida’s Citrus Canker Eradication Program in the late 1990s and early 2000s. Tahiti limes are being considered for reintroduction in Miami-Dade County because of the growing demand for this fruit, especially among buyers who are willing to pay more for Florida-grown fruit. In this publication, we explore the history of lime production in south Florida and current trends in the market, especially growing demand in the United States for Tahiti limes. The price premiums from the growing domestic market for Tahiti limes would likely be enough to overcome the challenges growers face in combating the disease pressure from citrus canker, citrus greening, and intense competition from Mexico and other countries.